Răspuns :
a+b+c=2895
a=b+23
b=c/2
=> c=2b
b+23+b+2b =2895
4b +23=2895
4b=2895-23
4b =2872 :4
b=718
a=b+23=718+23=741
c=2b=2×718=1436
a=b+23
b=c/2
=> c=2b
b+23+b+2b =2895
4b +23=2895
4b=2895-23
4b =2872 :4
b=718
a=b+23=718+23=741
c=2b=2×718=1436
x+y+z=2895
x=y+23, y=x-23
y=z/2, z=2y
inlocuim in prima ecuatie
y+23+y+2y=2895
4y=2895-23=2872, y=2872/4=718
x=718+23=741
z=2*718=1436
x=y+23, y=x-23
y=z/2, z=2y
inlocuim in prima ecuatie
y+23+y+2y=2895
4y=2895-23=2872, y=2872/4=718
x=718+23=741
z=2*718=1436